Diamonds and Warlords: The Geography of War in the Democratic Republic of Congo and Sierra Leone (Nordic Journal of African Studies, 2002)
The article offers a model of the dynamics of an internal war. The model is based on various views on military crises in developing countries and it offers a synthesis of the produce of the geography of war and conflict studies. The model describes several possible push and pull factors of war. It aims at constituting a new footstep for theorizing the dynamics of an internal war. Factors are surely numerous and all of them have not been elaborated here. Some factors can even simultaneously both push and pull countries into war. As the first elaboration of its kind, the model is hoped to paint a general picture on the dynamics of an internal war. (Ed.)